A portrait of the artist as Australian : l'oeuvre bizarre de Barry Humphries - St. Pierre, Paul Matthew, 1953- (McGill-Queen's University Press, 2004)
A Portrait of the Artist as Australian offers the first critical assessment of Barry Humphries' entire career - as a daring postmodern deconstructionist on stage, film, and television, with sixty-seven stage shows, twenty-four film and thirty-four video appearances, thirty-four television series and seventy-one television appearances, and seventy-two audio recordings, but especially what he calls his "second career" as author of twenty-nine books. With an oeuvre that includes novels, biographies, autobiographies, editions, compilations, comic books, poetry, dramatic monologues, sketches, film scripts, and several unclassified works, Humphries is a literary and dramatic artist of considerable significance. Arguing that Humphries is one of Australia's greatest writers, Paul Matthew St Pierre reveals a multi-faceted artist whose success is rooted in music halls, Dadaism, and his identity as an Australian.